PERANCANGAN PUSAT KAJIAN STUDI ISLAM TERPADU DI KOTA GORONTALO DENGAN PENDEKATAN SUSTAINABLE ARCHITECTURE - Irham Marada; Fikry Adam; Bakhtiar Bakhtiar (Universitas Negeri Gorontalo, 2023)
Gorontalo Province is an area where the majority of the population is Muslim and is known as the Veranda City of Medina. The problem is how the government can realize the development of an Integrated Center for Islamic Studies in Gorontalo Province, because this is the big dream and hope of the people of Gorontalo. The development of the Center for the Study of Islamic Studies in the City of Gorontalo should be designed to minimize the negative impact on the building environment with efficiency and moderation in the use of materials, energy, space and ecosystems where all of this can be realized by implementing an approach to sustainability. This study uses qualitative data collection methods and contextual design analysis methods as a comprehensive process. The end result of this research is the realization of a design concept that will be used in the design of the Integrated Islamic Studies Center in Gorontalo Province. Keywords: Islam,Gorontalo City, Sustainable Architecture